Concurrence of osteonecrosis and steroid myopathy secondary to oral steroid therapy in a patient with ABCB1 gene polymorphisms: A case report - Hu, Yidan; Lu, Chenyang; Lin, Hui (Frontiers in Endocrinology, 2022)
Glucocorticoids (GCs) are widely used in various autoimmune diseases. Side effects may occur in patients with long-term or high-dose GC usage. Among them, steroid myopathy and osteonecrosis are two severe forms. We report a patient with pemphigus vulgaris on GC-treatment who developed muscle weakness when a cumulative dose of methylprednisolone reached about 20g (14-80mg/d for 2.5 years). Laboratory tests showed slightly elevated lactate dehydrogenase and hydroxybutyrate dehydrogenase. MRI revealed osteonecrosis in the femoral head, distal femur, and proximal tibia of both legs. The biopsy of the right quadriceps revealed atrophy of type II myofiber without leukocyte infiltration, which was suggestive of steroid myopathy. Genotyping of the patient showed 5G/5G genotype of the PAI-1 gene and CC genotype of the ABCB1 gene (C3435T), suggesting she was sensitive to GCs. The patient’s lesions were considered to be GC-induced adverse events, which were improved with tapering GC. Therefore, it is important to recognize steroid-induced musculoskeletal side effects and genotyping favors personalized medication.